Authentic Assessment Techniques in IPAS Learning in Elementary School : A Case Study - Cholifah, Nur; Atmoko, Adi; Bustamam, Mardhatillah; Kusumaningrum, Shirly Rizki (Jurnal Paedagogy, 2024)
This research aims to describe the authentic assessment techniques coveyring cognitive, affective, and psychomotor aspects in IPAS learning in elementary schools. This research used a qualitative approach with a descriptive method. The design used in this research is a case study, in which researchers reveal and analyze holistically to get specific results. The subjects contained in this study are educators as homeroom teachers who are also IPAS teachers, students, and school principals. The data collection carried out in this study is using primary sources which include observation and interviews. Secondary sources included journals, books, and scientific articles. Data analysis conducted in this research is descriptive analytic. The results obtained in this study are based on the cognitive aspects of educators using written test assessment techniques, oral tests, and assignments. Affective aspects educators use observation, self-assessment, peer assessment, and journal assessment techniques. As well as psychomotor aspects, educators use project and portfolio assessment techniques. The achievement of learner competence can be seen based on the three aspects and the level of learning success is an integral part of the educational process.